'Going back to history': Haiti and US military humanitarian knowledge production. Issue 2 (4th May 2018) - Greenburg, Jennifer
ABSTRACT: This article focuses on how contemporary US military trainings 'go back to history' as they prepare military personnel for counterinsurgency and humanitarian response. Through ethnographic observations of trainings on US military bases, I discuss how military instructors train troops to manage civilians by drawing on the colonial history of 'small wars'. In these uses of history, instructors produce a particular military 'geographical imagination' that erases differences between specific historical geographies. Instructors argue that interchangeable tactics can be applied to any time, any place, any deployment, whether it is humanitarian or counterinsurgent. In contrast to this military spatial imaginary that effectively erases colonial history, I focus here on Haiti's role in producing military humanitarian knowledge. Haiti offers a critical geography of counterinsurgency that reveals humanitarian response as a particular theatre for rehearsing counterinsurgency tactics. Haiti's position within a critical geography of counterinsurgency calls into question military theorists' promotion of a future that looks like the colonial past.